Tata kelola perusahaan, iklim etika, dan deteksi penipuan: tinjauan literatur komprehensif tentang pencegahan dan deteksi penipuan akuntansi - Sinaga, Greace Leroy; Harahap, Muhammad Rizky; Mappadang, Agoestina (Jurnal Akuntansi dan Manajemen, 2026)
Accounting fraud undermines financial reporting integrity and public trust. Effective prevention and detection require more than traditional auditing, involving corporate governance, ethical climate, and adaptive detection systems. This research employs a Systematic Literature Review (SLR) of 21 publications (2015–2025) sourced from Scopus, Web of Science, and ScienceDirect to investigate the interrelation of these elements in combating accounting fraud. Findings show that robust governance structures, strong organizational ethics, and technological tools like forensic audits and data analytics significantly reduce fraud risk. The study highlights the need for synergy among governance, ethics, and technology to build a sustainable fraud prevention framework.